Histone Deacetylase Activity and the Renin-Angiotensin-Aldosterone System: Key Elements in Cardiorenal Alterations Provoked by Chronic Malnutrition in Male Adult Rats - Muzi-Filho, Humberto; Jannuzzi, Larissa B.; Bouzan, Ana C.S.; Alves-Barros, Sarana; Alves-Bezerra, Danilo S.; Pereira-Acácio, Amaury; Ferreira, Bruna S.N.; Silva-Pereira, Debora; Costa-Sarmento, Gloria; Vieyra, Adalberto (Cellular physiology and biochemistry, 2020)
BACKGROUND/AIMS: Chronic malnutrition (M) affects >1 billion people worldwide. Epidemiological data point to long-term renal and cardiovascular outcomes (e.g. arterial hypertension, cardiorenal syndromes). The renin-angiotensin-aldosterone system (RAAS) has been implicated in the physiopathology of these disturbances, but M-induced alterations in RAAS-modulated renal Na+ handling and their cardiovascular repercussions are not known. Moreover, altered tissue-specific histone deacetylases (HDAC) results in arterial hypertension and the use of sodium Valproate (Val; a HDAC inhibitor) reduces blood pressure. However, there are no reports regarding the renal and cardiovascular effects of HDAC inhibition in M, or on the signaling pathways involved. The central aim of our study has been to investigate whether alterations in the HDAC/RAAS axis underpin alterations in active Na+ transport in the kidney and heart, and affects blood pressure. METHODS: Male rats aged 28 days were given either a control (C) or a multideficient diet (Regional Basic Diet, RBD), which mimics alimentary habits from developing countries. Subgroups received Losartan (Los), a blocker of type 1 Angiotensin II receptors. When the rats reached 70 days, new subgroups received Val until they were 90 days of age. Homogenates and enriched plasma membrane fractions from renal cortex corticis and cardiomyocytes were obtained by differential centrifugation of the tissues. The activity of renal and cardiac deacetylases was assayed by measuring - after incubation with the membranes - the amount of deacetylated lysines in a substrate containing an acetylated lysine side chain. Protein kinases activities were measured following the incorporation of the γ-phosphoryl group of [γ-32P]ATP into Ser/Thr residues of histone type III-S. The activity of Na+-transporting ATPases (kidney and heart) was quantified by measuring the release of Pi from ATP that was sensitive to ouabain ((Na++K+)ATPase), or sensitive to furosemide (Na+-ATPase). Tail-cuff plethysmography was used to measure systolic blood pressure and heart rate. RESULTS: M provoked HDAC downregulation, which was reversed by Los and Val, either alone or in combination, with selective upregulation of protein kinases C and A (PKC, PKA) in renal cortex corticis, but not in left ventricle cardiomyocytes. The 2 kinases were strongly inhibited by Los and Val in both organs. Malnourished rats developed elevated systolic arterial pressure (SAP) and heart rate (HR) at 70 days of age; Los and Val restored the control SAP, but not HR. Functional and the above biochemical alterations were associated with the deregulation of renal and cardiac Na+-transporting ATPases. (Na++K+)ATPase activities were downregulated in M rats in both organs, and were further inhibited by the pharmacological treatments in the renal cortex corticis (C and M groups) and the left ventricle (only in C rats). No additional effect was found in cardiac (Na++K+)ATPase from M rats. Ouabain-resistant Na+-ATPase was upregulated in renal cortex corticis and downregulated in cardiomyocytes, returning to C values after administration of Los and Val. CONCLUSION: The HDAC/RAAS axis appears to be a key regulator of Na+-transporting ATPases in renal cortex corticis and cardiomyocytes via an appropriate balance of PKC and PKA activities. Modifications within the HDAC/RAAS axis provoked by chronic M - with repercussions in renal and cardiac Na+ transport - underpin alterations in bodily Na+ homeostasis that culminate with the onset of arterial hypertension and potential cardiorenal syndrome.